Computational analysis of the flexibility in the disordered linker region connecting LIM domains in cysteine–glycine-rich protein - Chauhan, Pankaj Kumar; Sowdhamini, R. (Frontiers in Genetics, 2023)
One of the key proteins that are present in the Z-disc of cardiac tissues, CSRP3, has been implicated in dilated and hypertrophic cardiomyopathy leading to heart failure. Whereas multiple cardiomyopathy-related mutations have been reported to reside on the two LIM domains and the disordered regions connecting the domains in this protein, the exact role of the disordered linker region is not clear. The linker harbours a few post-translational modification sites and is expected to be a regulatory site. We have carried out evolutionary studies on 5614 homologues spanning across taxa. We also performed molecular dynamics simulations of full-length CSRP3 to show that the length variations and conformational flexibility of the disordered linker could provide additional levels of functional modulation. Finally, we show that the CSRP3 homologues with widely different lengths of the linker regions could display diversity in their functional specifications and selection of interacting protein partners. The present study provides a useful perspective to our understanding of the role of the disordered region between CSRP3 LIM domains and their evolution.